Diversity And Characterization Of Ralstonia Solanacearum Strains In Peninsular Malaysia - Khakvar, Reza (2009)

(untitled)
Surveys were conducted between the years of 2005 and 2007 at several locations in the northern, central and southern parts of West Malaysia to study the molecular characteristics of Ralstonia solanacearum strains. These sampling sites included vegetable farms and known hosts of the pathogen, such as banana, tomato, eggplant, chili and tobacco. Samples were collected from the suspected wilted plants and weeds, including soil and water samples, at the same areas. The bacterium was isolated from all samples using semi-selective medium and identified using BIOLOG identification system. A two-stage nested-PCR was performed to confirm the results of BIOLOG test. The first PCR run produced a 410 bp amplicon and the second run produced 220 bp for all positive samples. Therefore all the strains were further confirmed as R. solanacearum. A total of 69 strains were confirmed as R. solanacearum by BIOLOG identification system and nested-PCR. Thirty-two or 46.3% of positive samples were isolated from banana followed by chili (15.9%), tomato (13%), eggplant (7.2%) and tobacco (1.45%). Using routine biochemical tests, 38 and 31 strains have been recognized as Biovar 3 and biovar 4 respectively. Pulsed Field Gel Electrophoresis (PFGE), BOX-PCR and Fatty acid methyl ester (FAME) were used to determine the relatedness among these strains. All strains of R. solanacearum were typeable by PFGE and produced discernable banding patterns consisting of bands ranging from 15 to 800 kb. High similarity was observed among the strains from the same geographic regions. The strains that were collected from Terengganu (in northeast of West Malaysia) showed the highest similarity. Based on the PFGE analysis, strains of biovar 4 showed little variation in fingerprinting than strains of biovar 3. All strains except banana strains were divided into two main clusters in which each cluster consisted of pathogenic or non-pathogenic strains separately. All of the strains were also typeable by BOX-PCR fingerprinting method and in total 19 reproducible bands, ranging from 480 to 3200 bp, were scored and used for analysis. The similarity of patterns varied from 60 to 95%. Cluster analysis of the BOX-PCR patterns revealed same similarity with PFGE among all strains. The results of FAME analysis showed that fatty acid composition were very variable. Nine types of fatty acids were identified and quantified among all strains. Seven out of these nine fatty acids were identified as dominant fatty acids which consisted 98% of total fatty acids. Euclidean distances were calculated and the results showed that all FAME clusters were highly correlated with host and pathogenicity of bacterial strains but low correlation was found between biovar and FAME clusters. A unique FAME profile was found among the strains that have been isolated from banana. This study clearly showed that R. solanacearum strains were phylogenetically similar within a region but diverse between regions despite biovar designation. Furthermore, fingerprinting by PFGE, BOX-PCR and FAME revealed a unique genomic and phenotypic distance within pathogenic and non-pathogenic strains of bacterium which previously was unrealized.